The association between income and life expectancy revisited: deindustrialization, incarceration and the widening health gap - Nosrati, E; Ash, M; Marmot, M; McKee, M; King, LP (Oxford University Press, 2017)
Background The health gap between the top and the bottom of the income distribution is widening rapidly in the USA, but the lifespan of America’s poor depends substantially on where they live. We ask whether two major developments in American society, deindustrialization and incarceration, can explain variation among states in life expectancy of those in the lowest income quartile. Methods Life expectancy estimates at age 40 of those in the bottom income quartile were used to fit panel data models examining the relationship with deindustrialization and incarceration between 2001 and 2014 for all US states. Results A one standard deviation (s.d.) increase in deindustrialization (mean = 11.2, s.d. = 3.5) reduces life expectancy for the poor by 0.255 years [95% confidence interval (CI): 0.090–0.419] and each additional prisoner per 1000 residents (mean = 4.0, s.d. = 1.5) is associated with a loss of 0.468 years (95% CI: 0.213–0.723). Our predictors explain over 20% of the state-level variation in life expectancy among the poor and virtually the entire increase in the life expectancy gap between the top and the bottom income quartiles since the turn of the century. Conclusions In the USA between 2001 and 2014, deindustrialization and incarceration subtracted roughly 2.5 years from the lifespan of the poor, pointing to their role as major health determinants. Future research must remain conscious of the upstream determinants and the political economy of public health. If public policy responses to growing health inequalities are to be effective, they must consider strengthening industrial policy and ending hyper-incarceration.